Beliefs and self-reported practice of footcare among persons with type II diabetes mellitus attending selected health centres in east Trinidad - Rachel Leah Vincent-Edinboro; Philip Onuoha (SpringerOpen, 2022)
Abstract Background It has been documented that nearly 600 million people worldwide are expected to have diabetes mellitus in 2035 and that approximately 140,000 persons aged 20-69 years living with diabetes mellitus in Trinidad and Tobago. It is also indicated that patients with type II diabetes mellitus face a higher risk of diabetic foot neuropathy and foot ulcers which increase the risk of below the knee amputation in persons living with diabetes. Purpose The aim of this research project was to explore the beliefs related to footcare and the self-reported footcare practice of persons with type II diabetes mellitus attending selected health centres in East Trinidad. Method A survey was used to explore the footcare beliefs and the self-reported footcare practice of persons with type II diabetes mellitus attending selected health centres in East Trinidad (n = 87). Results Participants had strong belief regarding susceptibility to foot injury, strong belief regarding the seriousness of complications of foot injury, reported good footcare practice and excellent practice of overcoming barriers to performing footcare. There is a correlation between the belief regarding susceptibility to a foot injury and age (p ≤ 0.05). Also, there is a significant correlation between belief regarding susceptibility to a foot injury, seriousness of complications and self-reported footcare practices (p ≤ 0.05). Conclusion This study explores and describes the beliefs and self-reported practices of footcare among individuals with type II diabetes mellitus at selected health centres in East Trinidad. It supports the Health Belief Model as an effective framework for the promotion of appropriate footcare among persons with type II diabetes mellitus.